REFLECTIONS ON THE REURBANISM PARADIGM: RE-WEAVING THE URBAN FABRIC FOR URBAN REGENERATION AND RENEWAL - Haas, Tigran; Locke, Ryan (Quaestiones Geographicae, 2018)
Within the realm of contemporary urban design theory and practice, a number of authors have conceptualised the trends and processes of city development and planning into a series of urbanisms. This discussion essay examines the overall tenets of the ‘ReUrbanism paradigm’, a paradigm that has long been present in city planning and development but has received limited analysis and criticism and has not gained a more integrated position within the professional and academic worlds. This paper continues a paradigm development outline, leaning on the characteristics of other urbanisms in order to develop and provide a frame of reference and to contribute to the ongoing build-up of taxonomies about the trajectory of contemporary urban design thought. Focusing on the American representative case of Detroit, the authors of this paper argue for a better understanding of this urban regeneration paradigm, which they characterise as a rational urban planning & design approach in the contemporary age of inner city renewal.